2011
DOI: 10.1002/oa.1124
|View full text |Cite
|
Sign up to set email alerts
|

Childhood scurvy in a medieval burial from Mačvanska Mitrovica, Serbia

Abstract: The type and distribution of abnormalities in the skeleton of a child 2 years of age indicates that the child likely suffered from scurvy at the time of death. The burial is from the archaeological site of Zidine, Mač vanska Mitrovica, Serbia dated to the Medieval Period. Abnormal porosity and reactive woven bone formation are present affecting both the axial and appendicular skeleton. This case of scurvy is important because archaeological evidence of scurvy in this geographical location and at this time peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 24 publications
5
32
0
3
Order By: Relevance
“…They note that definitive diagnoses were made on individuals that displayed pathological changes to the maxilla, sphenoid bone and mandible (Geber & Murphy, : 515–516). Orbital lesions involving new bone formation are associated with scurvy, but not as strongly (Brown & Ortner, ; Geber & Murphy, : 515–516).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…They note that definitive diagnoses were made on individuals that displayed pathological changes to the maxilla, sphenoid bone and mandible (Geber & Murphy, : 515–516). Orbital lesions involving new bone formation are associated with scurvy, but not as strongly (Brown & Ortner, ; Geber & Murphy, : 515–516).…”
Section: Methodsmentioning
confidence: 99%
“…They describe diagnostic abnormal porosity of the sphenoid bone, mandible, maxilla and orbits. However, none of these are listed as strongly diagnostic, and many researchers generally caution that multiple indicators of scurvy should be assessed to aid 761 Presence and Absence in a secure diagnosis of the condition (Brown & Ortner, 2011;Geber & Murphy, 2012;Ortner et al, 1999). The analysis by Geber & Murphy (2012), which reports the presence of features associated with scurvy in a collection of 19th-century Irish individuals, including some incomplete remains, provides the basis for the following study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Scurvy is increasingly being identified in past child populations from around the world (e.g. Brown and Ortner 2011;Klaus 2014). Mays (2014) undertook a timely review of the current level of palaeopathological knowledge about the disease which demonstrated how it is very much a disease of children unless the population has derived from a group living in conditions of extreme hardship, such as might be caused by famine or prolonged sea voyages.…”
Section: The Palaeopathology Of Childhoodmentioning
confidence: 99%
“…These criteria have been used in numerous studies (e.g. Ortner et al, 1999Ortner et al, , 2001Melikan and Waldron, 2003;Brickley and Ives, 2006;Brown and Ortner, 2011;Geber and Murphy, 2012).…”
Section: Introductionmentioning
confidence: 99%